Crucial Role of Increased Arid3a at the Pre-B and Immature B Cell Stages for B1a Cell Generation - Hayakawa, Kyoko; Li, Yue-Sheng; Shinton, Susan A.; Bandi, Srinivasa R.; Formica, Anthony M.; Brill-Dashoff, Joni; Hardy, Richard R. (Frontiers in Immunology, 2019)
The Lin28b+Let7– axis in fetal/neonatal development plays a role in promoting CD5+ B1a cell generation as a B-1 B cell developmental outcome. Here we identify the Let7 target, Arid3a, as a crucial molecular effector of the B-1 cell developmental program. Arid3a expression is increased at pro-B cell stage and markedly increased at pre-B and immature B cell stages in the fetal/neonatal liver B-1 development relative to that in the Lin28b–Let7+ adult bone marrow (BM) B-2 cell development. Analysis of B-lineage restricted Lin28b transgenic (Tg) mice, Arid3a knockout and Arid3a Tg mice, confirmed that increased Arid3a allows B cell generation without requiring surrogate light chain (SLC) associated pre-BCR stage, and prevents MHC class II cell expression at the pre-B and newly generated immature B cell stages, distinct from pre-BCR dependent B development with MHC class II in adult BM. Moreover, Arid3a plays a crucial role in supporting B1a cell generation. The increased Arid3a leads higher Myc and Bhlhe41, and lower Siglec-G and CD72 at the pre-B and immature B cell stages than normal adult BM, to allow BCR signaling induced B1a cell generation. Arid3a-deficiency selectively blocks the development of B1a cells, while having no detectable effect on CD5– B1b, MZ B, and FO B cell generation resembling B-2 development outcome. Conversely, enforced expression of Arid3a by transgene is sufficient to promote the development of B1a cells from adult BM. Under the environment change between birth to adult, altered BCR repertoire in increased B1a cells occurred generated from adult BM. However, crossed with B1a-restricted VH/D/J IgH knock-in mice allowed to confirm that SLC-unassociated B1a cell increase and CLL/lymphoma generation can occur in aged from Arid3a increased adult BM. These results confirmed that in fetal/neonatal normal mice, increased Arid3a at the pre-B cell and immature B cell stages is crucial for generating B1a cells together with the environment for self-ligand reactive BCR selection, B1a cell maintenance, and potential for development of CLL/Lymphoma in aged mice.